Iniciativas governamentais de apoio aos emigrados : o caso de Brasil e Itália em perspectiva comparada - Ribeiro, Carla Alexsandra do Carmo (2016)
Nowadays, international migration is an important issue. Many academics relate migration to international security, labour market, cultural assimilation or public policy. The aim of this paper was understand how labour migration is seen by origin country and how State treats its citizens abroad through actions to support them. Citizens have rights and duties. When they migrate some aspects persist: either their duties referring to documents in general, passports and, income tax or their rights such as vote for President, assistance and protection from origin country are diplomatic, economic, political and social ties. The question is: what else? The object of this study is government initiatives to support emigrants, excepting international agreements, because it sought the initiatives from States which would meet demands of migrants specifically. Comparative and documentary research methods were chosen as tools to organize and structure this Dissertation. It was necessary to choose another country to compare these initiatives. Thus, Italy was chosen because its migration history resembles Brazil and even today Italians migrate to other EU countries with the same motif: work. Moreover, Italians’ initiatives are not so close Brazilians ones. For instance, while Brazil has just initiatives to support citizens abroad, Italy has initiatives to migration return: financial resources to rent a house, to pay for education or health. Remittances are important to migrants as well as State. On one hand, when migrants send money to their families left behind they provide sustainable economic and social development because their families purchase necessities such as food, clothing and housing. On the other hand, workers’ remittances are important for developing countries because it has become a major external source of funds. Another interesting feature of both countries refers to registration system from Italy what provide a real idea of its diaspora while decentralized system from Brazil affect its outcomes. The conclusion is a reflection about how States relate to its citizens abroad.